Interactive tutorial for calculating cable ampacity - Bascom, E.C.; Rodenbaugh, T.J.; Brown, H.J. (IEEE computer applications in power, 1991)
The Cable Ampacity Tutorial (CABAMP), which describes the procedure for calculating the steady-state ampacity (current) rating of underground transmission cable systems, is discussed. This interactive tool allows engineers to reference the tutorial at the same time they are performing calculations. It provides instructions for calculating steady-state ampacity of underground transmission pipe-type, self-contained, and extruded power cables. In the workstation mode, the tutorial provides guidance for performing rigorous ratings calculations through a common database with other programs.< >